Raging storm [large type] - Chapman, Vannetta (The remmant series, 2017)
"After a solar flare has wiped out all modern technology, Shelby Sparks and Max Berkman team up to face the dangers of Austin in search of medication for Shelby's diabetic teenage son. Survival will be threatened and faith will be put to the ultimate test as a raging storm engulfs America"--